ASEAN Centrality in AUKUS Study Case - Akmal Tawakal (Journal of Diplomacy and International Studies, 2022)
This article aims to explain how ASEAN centrality position in response to AUKUS Pact. This article using security dilemma concept and problem of comparison in comparative regionalism concept to analyze problem that threatening Indo-Pacific and how ASEAN manage to solve security problem. The research method used in this article is analytical descriptive qualitative with study case approach, where action by some of the states in Southeast Asia support and criticize the regulation in AUKUS Pact. Techniques of data collecting of this article is through literature such as books and journals with some sources from the internet. The result of this article showed that AUKUS Pact establishment has threatened Indo-Pacific region and cause security dilemma especially in North Natuna Sea. The response from ASEAN member to AUKUS showed how fragile the ASEAN centrality is and it need to be more strengthening specifically in terms of region security problem in Indo Pacific.